Hardware Design of PIC Microcontroller based Charge controller and MPPT for the Standalone PV-Battery charging System - Santhosh, Rahul; Sabareesh, S U; Aswin, R; Mahalakshmi, R. (2021 International Conference on Recent Trends on Electronics, Information, Communication & Technology (RTEICT), 2021)
Solar power is clean and is safe for the environment. There are many challenges in converting solar energy into electricity. Temperature and solar irradiance are the important factors that affect the output performance of a photovoltaic (PV) system. There are different PV system topologies such as standalone and grid connected PV system. This paper focuses on standalone PV system. In standalone PV system, the storage of solar electricity through battery is playing major role. This paper illustrates the complete design of prototype model of the standalone PV-battery charging scheme with MPPT and Charge controller. The proposed PV charging scheme uses PIC microcontroller PIC16F877A based charge controller for regulating the battery charging by limiting the overcharging current and to protect the battery from over charging. Also this control uses incremental conductance based Maximum Power Point Tracker (MPPT) method. Control algorithm for PIC controller is discussed in this paper.